Spatio-temporal dynamics of the zooplankton community of the Mondego estuary - Santos, Leonardo Valente dos (2017)
Estuaries are among the most valuable and productive aquatic systems in terms of their services to human welfare. In the last decades it has been highlighted the importance of plankton (and mainly zooplankton) in the dynamic of aquatic food webs. Zooplankton plays a pivotal ecological role in terms of biomass and energy fluxes transference between primary producers and higher trophic levels, being raised the importance of this group in ecological studies. Furthermore, spatio-temporal scales of zooplankton communities’ structure and composition are an important focus in ecological research. Thus, the main aim of this work was to study the spatio-temporal dynamics and vertical distribution of zooplankton community in the Mondego estuary (Portugal), based on monthly field surveys conducted from May 2012 to March 2014, at the bottom and surface, with a mesh net size of 335 μm, in high tide. In addition, the influence of environmental variables (e.g. temperature, salinity, nutrients concentration) in the distribution of zooplankton communities was determined. The occurrence of a extreme climate events (drought and flood conditions) during the study period also allowed examining the effects of the extreme weather conditions on zooplankton ecology. The results showed variations in the distribution and abundance of various zooplankton groups related to drought and flood conditions during the studied period. The main variation in environmental parameters was register to the salinity and temperature levels, leading to the predominance of marine species during drought events. It was also possible to identify that these variations occur in the bottom and surface communities, however, at the bottom was not registered so drastic changes compared to the zooplankton composition from the surface.